Children's artistic expression in times of war: A challenge for historical and educational research - Padrós, Núria; Casanovas Prat, Josep (Historia y Memoria de la Educación, 2025)
This paper is based on the study of children's artistic productions produced during the Spanish Civil War. The main source is the collection of drawings from the Grupo Escolar Lluís Vives, a school in a working-class neighbourhood of Barcelona. This collection has been contrasted with the paintings and illustrations of José García Narezo, a precocious child artist who received unusual recognition during the war at the International Exhibition of Plastic Arts in Paris in 1937, where his works were displayed in the Pavilion of the Republic. The analysis of these artistic productions allows for a better understanding of the experiences lived by these children in a crucial period of history and, at the same time, to reflect on the challenges that have defied the ethical positions and the way of approaching the different dilemmas that appeared during the previous research process, as well as broadening the perspective on the influence of the context on children's representations. These challenges allow for new questions in educational-historical research and call upon the researchers, especially when involving children and their artistic productions. The article shows that children's artistic expression as a source of study is a way of listening to the voice of childhood, considering children as active subjects in history.